Study about the emotional valence of environmental concepts using affective priming technique - Sánchez Miranda, Martha Patricia; De La Garza González, Arturo; Rangel Sandoval, María Lilia (2013)
A quasi-experimental study was conducted with the affective priming technique in 62 students of psychology of a Mexican public university in order to determine if this paradigm is able to detect differences in emotional valence using related words to the natural and urban environments, when these are presented as congruent and incongruent primings to the target words. The findings suggest that exist two groups within the same sample by the kind of response to the positive priming of the nature, but it did not show the difference of the city assessment. It also shows an unexpected evaluation to the negative priminig of the city. Possible explanations to the phenomenon are discussed and the findings are compared with others researchers reports.